2001
DOI: 10.1016/s0002-9149(00)01308-4
|View full text |Cite
|
Sign up to set email alerts
|

Final results of a randomized trial comparing the MULTI-LINK stent with the Palmaz-Schatz stent for narrowings in native coronary arteries

Abstract: The MULTI-LINK (ML) stent is a novel second generation coronary stent. The ACS MultiLink Stent Clinical Equivalence in De Novo Lesions Trial (ASCENT) randomized 1,040 patients with single, de novo native vessel lesions to treatment with the ML stent or the benchmark Palmaz-Schatz (PS) stent, to demonstrate that the ML stent was not inferior to (i.e., equivalent or better than) the PS stent in terms of target vessel failure by 9 months. Successful stent delivery was achieved in 98.8% versus 96.9% of patients, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
2
5

Year Published

2001
2001
2005
2005

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 16 publications
3
36
2
5
Order By: Relevance
“…25 BAR rates and TLR rates ranging between 15% and 25% for stents and between 20% and 40% for other angioplasty devices [5][6][7][8] allowed detection of modest differences in restenosis rates in clinical trials of fewer than 1000 subjects. 26,27 The evaluation of restenosis in the DES era is more complex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 BAR rates and TLR rates ranging between 15% and 25% for stents and between 20% and 40% for other angioplasty devices [5][6][7][8] allowed detection of modest differences in restenosis rates in clinical trials of fewer than 1000 subjects. 26,27 The evaluation of restenosis in the DES era is more complex.…”
Section: Discussionmentioning
confidence: 99%
“…1,31 Bare metal stent trials and registries have demonstrated mean late losses varying from 0.6 to 1.2 mm. 5,6,26,27,[32][33][34][35] The RAVEL trial of the sirolimus-eluting Bx Velocity stent was the first randomized trial to report a stent with an average late loss well below the expected historical range, as well as its own control arm (in-stent late loss Ϫ0.01 mm active versus 0.80 mm control), which corresponded to a BAR rate of 0% for the active arm versus 26% in the control arm. 36 As the positive mean of any normal distribution is reduced enough so that its spread becomes significantly bounded by zero, it becomes right-skewed.…”
Section: Late Loss and Its Skewed Distribution For Dessmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Angiographic studies in patients treated with BMS have reported binary restenosis rates within the stent and within the treated arterial segment that included its nonstented margins. 6,7 Although previous BMS stent studies did not examine the specific lumen changes at the proximal or distal nonstent margins, intravascular ultrasound studies have shown that balloon injury proximal and distal to the stent may result in lumen renarrowing resulting from arterial remodeling at the edges of the stent. 9 Studies evaluating angiographic outcomes in patients undergoing radiation brachytherapy or using radioactive stents have also shown that proliferation at the stent edges may be associated with higher-than-expected restenosis rates at the stent margins ("candy wrapper effect") because of an untoward effect of low-dose radiation at the stent margins.…”
Section: Restenosis After Bms Implantationmentioning
confidence: 99%
“…The results of trials using the ACS MULTI-LINK (ML) stent (Guidant, Santa Clara, CA, USA), one of the recently developed stents, were similar to or slightly better than those of trials using the PS stent. 5,6 However, the follow-up periods in those trials were less than 9 months, so little is known about long-term (>12 months) outcome after ML stent implantation. The purpose of this study, therefore, was to evaluate the relatively long-term clinical outcome (2 years) of patients with coronary artery disease treated with the ML Circulation Journal Vol.66, October 2002 stent and to determine independent factors correlated with target lesion revascularization and cardiac events.…”
mentioning
confidence: 99%